We Have to Talk: "Doing" Critical Literacy in Class and in Community - Rebecca L. Pearson (SLACK Incorporated, 2017)
My faculty responsibility includes continuing my own education-about my discipline and about how I can best support students, through my teaching, to the careers they want. My newest learning surrounds critical literacy, which I best understand as knowing (and being able to act on) what you need to in order to do what you want to do for yourself or others (Mogford, Gould, & DeVoght, 2010; Sykes, Wills, Rowlands, & Popple, 2013). Critical literacy implies awareness of policy options, public health evidence, industry influence on regulation and research, and the like.